Prevalence of metabolic syndrome in workers of Medical Science college in Cienfuegos city. - Mikhail Benet Rodríguez; René Mick Cabrera Núñez; Patricio Castillo Sardiñas; Yudeny Poll Cañizares; Yadira Suaréz (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2005)
Introduction: Despite the many studies that have been carried out in the late 30 years on non transmitting diseases and the different cardiovascular risk factors, little have been published about metabolic syndrome. Objective: to determine the prevalence of metabolic syndrome in the worker population of the Faculty of Medical Sciences of Cienfuegos. Methods: A descriptive, correlating study was done, with a sample of 109 persons of both sex from the worker staff of the Faculty of Medical Sciences of Cienfuegos. The following variables were studied: sex, age, fasting glycaemia, HDL cholesterol, tryglicerids , arterial pressure, abdominal , and body mass index. Also, from these variables it was delimited the prevalence of metabolic syndrome. Results: it was observed that 26.5% of the population has elevated tryglicerids, the 38.8% has low rates of HDL cholesterol, and near 60% is obese. On the other hand, the 18.4% of the studied were considered as bearers of metabolic syndrome. Conclusions: the cardiovascular risk factors that more affect the workers of the Faculty of Medical Sciences of Cienfuegos are: obesity and low rates of HDL cholesterol. The prevalence of metabolic syndrome is high, similar to that of some developed countries.